A Study on Challenges for Adoption of Reverse Vending Machine: A Case of North Bengaluru, India (Proceedings of the World Conference on Waste Management, 2019)
India will be producing 80-85 MT of Solid waste by 2030. Given the alarming quantity it isimperative to bring in methods which will alleviate the problem especially the plastic waste. One of theproducts which helps in effective disposal of plastics is the Reverse Vending Machine (RVM). An RVM isa device which accepts bar coded plastic bottles and returns digital cash or redeemable coupons. The fieldstudy and literature show that reverse vending machine is not used extensively. This study attempts toexplore the challenges for adoption of eco-friendly products like RVM. A conceptual model was built usingthe variables identified through literature review. The variables identified included awareness, willingness,incentives, convenience and involvement. A survey was designed and data was collected from 246 citizensto understand their views. Structural Equation Modelling was used to test conceptual model. The resultsemphatically show that willingness to adopt RVM was influenced by factors of involvement, convenience,awareness and incentives in that order. It is also intuitive that when involvement is high then there is anattempt to become aware and adopt eco-friendly methods which is reiterated by the results. Hence citizenshave to get involved either by their own interest or by enforcing through legislation and policies to useRVM. The study concludes by recommending more policies and strategies like “bottle bill”, “EuropeanUnion Plastic Strategy” and Recycle Refund Systems to be mandated across the world to encouragecitizens to use methods which will keep our environment plastic free.
Keywords: Reverse Vending Machine; Willingness; Plastic; Convenience; Involvement